A comparison of microplastic pollution in different sites of sediment mangroves forests in Tung Prong Thong (Golden Meadow) - Vaz, Abrao De Jesus; Thammarat Koottatep; Guerro, Simon Cruz; Tatchai Pussayanavin; Government of Japan (Pathum Thani, Thailand : Asian Institute of Technology, 2022)
Plastic pollution has a major concern to global environmental security. But it does not stop there; what comes after is far worse. When the large pieces of plastic are discarded into the environment, these larger pieces of plastic break down into smaller pieces predominantly through mechanical and biological degradation, called microplastic. Microplastics are smaller particles less than 5 mm (0.2 inches) in diameter, they are widely spread in freshwater, terrestrial, and marine realm because of their small size and vast quantity (Sighicelli et al., 2018; Peng et al., 2018; Gong & Xie, 2020; Waller et al., 2017). Since the last decade, microplastics have gained significant attention as a new environmental pollutant and are ranked as the second most critical concern in environmental science and ecology (Horton et al., 2017, Farrell & Nelson, 2013). The issue with microplastic is that they do not easily degrade in a short time, but can take hundreds and thousands of years to decompose completely. poor waste management, these tiny particles could easily enter our natural environment and especially accumulate in the food chain. The observation and direct sampling, as well as laboratory tests of this research, were conducted on 09 May 2022. This study aims to examine the existence of microplastics, in the sediment of mangrove forests in Tung Prong Thong (Golden Meadow), Rayong province, based on their type, color, size, number, and abundance of microplastics by using PVC core sampler (Syakti et al., 2017). Microplastics are fragments of any type of plastic less than 5 mm in size, and in this research microplastics, were classified into 5 categories (Miller et al., 2021): soft particle, hard particle, fiber, transparent film, and opaque film. 707 items/kg d.w of microplastics were discovered: (170 items/kg d.w fibers), (126 items/kg d.w hard particles), (transparent film 165 items/kg d.w), (123 items/kg d.w, soft particles), and (123 items/kg d.w, opaque films). The most common color found are transparent and white. The size that was identified were small (<1mm) and large (>1-5 mm). The higher concentration of microplastics in mangrove forest Tung Prong Thong (Golden Meadow) was mainly related to inputs from the Same Phu River. The main activity alongside of Same Phu River is aquaculture such as farming, oyster farming, shrimp farming. Therefore, it has high change that aquaculture activity in this location is the main contribution source of microplastics in the mangrove sediment.
A research study submitted in partial fulfillment of the requirements for the degree of Master in Marine Plastics Abatement, School of Environment, Resources and Development
Research studies project report (M.) - Asian Institute of Technology, 2022
Keywords: Microplastics -- Environmental aspects -- Thailand -- Tung Prong Thong; Mangrove forests -- Thailand -- Tung Prong Thong